Evaluation of a cooling system integrated with different phase change materials and its effect on peak load shaving. (18th February 2021) - Riahi, Alireza; Kavian, Soheil; Mosleh, Hassan Jafari; Shafii, Mohammad Behshad
Summary: In this study, a vapor‐compression cooling system utilizing different phase change materials (PCMs) has been studied whereby the electricity consumption peak load is shifted. More specifically, the dynamic performance of cooling systems with and without using PCM is evaluated for the hottest day of the year. The proposed system uses the cooling energy to freeze, or "discharge" the PCM during nighttime when the cooling load is minimally needed and uses the stored thermal energy during the peak load hours by melting, or "charging" the PCM. This leads to better performance during peak load hours when higher cooling loads are needed. Different PCMs including oleic acid, SP224A, CL, CaCl2 ·6H2 O have been investigated. The system performance has been investigated by considering several parameters such as coefficient of performance, compressor power consumption, accessible cooling load, and melting fraction of PCM. The effect of different volumes of PCM on the average cooling cost has been evaluated, as well. The results indicated that with using the PCM, the accessible cooling load raises and the electricity consumption falls during hours of the peak load. Peak load reduction in the on‐peak period is different for various PCMs. In comparison with the conventional cooling system, the peak load alters from 315 W to 170, 164, 93, and 74 W for CL, oleic acid, CaCl2 ·6H2 O, and SP224A, respectively. The evaluation of different PCM illustrated that for the volume of 150 L, the peak load shaving for SP224A is the most value which is 76.3%. Moreover, while the volume of different PCMs increases, the average price of the cooling energy decreases, and the Levelized cost of cooling energy rises. Abstract : In this study, a new vapor compression cooling cycle integrated with phase change material (PCM) heat exchanger and control valves have been introduced. Depending on the discharge or charge mode, the PCM heat exchanger act as an auxiliary heat exchanger before the condenser or cooling storage before the evaporator. The switching valve alters the position of the PCM in the closed cycle depending on the peak or off‐peak periods.